Exhumation and landscape evolution in eastern South China since the Cretaceous: New insights from fission-track thermochronology. (15th April 2020) - Wang, Yang; Wang, Yuejun; Li, Shubo; Seagren, Erin; Zhang, Yuzhi; Zhang, Peizhen; Qian, Xin
Graphical abstract: Highlights: Eastern South China was paleo-highland and experienced regional exhumation in the Cretaceous. Insignificant exhumation, peneplanation, and local sedimentation occurred in the Paleogene. Rapid exhumation, topographic tilting, and climatic transition commenced in the late Oligocene. Abstract: Widespread extensional half-/grabens with red bed sedimentation, dome structures, and magma intrusions/eruptions with polymetallic mineralization within South China during the Cretaceous-Cenozoic provide a natural laboratory to understand intracontinental deformation and plate tectonics. In order to decipher the tectonic and landscape evolution of eastern South China, this study presents new low-temperature thermochronology from a broad region covering major tectonic units including the Xuefeng, Jiuling, Nanling, and Wuyi mountains. Zircon and apatite fission track dates, length distribution, and thermal history modeling reveal a prominent and rapid cooling phase during ~125–80 Ma across the paleo-highland in eastern South China. A synthesis of existing thermochronologic data and geological observations suggests that NE/NNE-striking syn-sedimentary faults system with half-/graben basins, rapid exhumation of Cretaceous magma and pre-Cretaceous basement, and final extension of dome structures were all initiated in a back-arc setting during this period (~80-125 Ma). Eastern South China during the Paleogene was characterized by a tectonic quiescence during which insignificant exhumation, peneplanation, and local sedimentation occurred, forming regional low-amplitude, long-wavelength topography. Accelerated regional cooling commenced in the late Oligocene or early Miocene in response to the far-field effect of the India-Asia continental convergence. Additionally, the termination of red-colored gypsum-salt-bearing sediment in the Neogene suggests a paleo-environmental change within South China, from an arid to a monsoonal climate; such change was likely the result of the topographic uplift of the Tibetan Plateau and its margins.